2021
DOI: 10.1146/annurev-cancerbio-060820-090737
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Preconditioning in Cancer Treatment in Relation to DNA Damage and Aging

Abstract: Dietary restriction (DR) is the most successful nutritional intervention for extending life span and preserving health in numerous species. Reducing food intake triggers a protective response that shifts energy resources from growth to maintenance and resilience mechanisms. This so-called survival response has been shown to particularly increase life and health span and decrease DNA damage in DNA repair–deficient mice exhibiting accelerated aging. Accumulation of DNA damage is the main cause of aging, but also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 128 publications
1
9
0
Order By: Relevance
“…If, however, the number of DNA lesions becomes too high for the repair machineries to tackle, patients treated with various DNA damaging treatments such as radio-and chemotherapy would be left with elevated levels of persisting DNA lesions. The chemotherapy side-effects observations made in Table 1 strengthen the hypothesis that elevated exposure would lead to accelerated aging later in life [12,15,156] and is in line with the DNA damage theory of aging [155,163]. Likewise, children with inborn mutations in DNA repair processes or nuclear integrity show segmental progeroid aging, affecting only a subset of tissues and organs [157,[164][165][166].…”
Section: Conceptualization Of Chemotherapeutics Driving Segmental Agingsupporting
confidence: 69%
See 2 more Smart Citations
“…If, however, the number of DNA lesions becomes too high for the repair machineries to tackle, patients treated with various DNA damaging treatments such as radio-and chemotherapy would be left with elevated levels of persisting DNA lesions. The chemotherapy side-effects observations made in Table 1 strengthen the hypothesis that elevated exposure would lead to accelerated aging later in life [12,15,156] and is in line with the DNA damage theory of aging [155,163]. Likewise, children with inborn mutations in DNA repair processes or nuclear integrity show segmental progeroid aging, affecting only a subset of tissues and organs [157,[164][165][166].…”
Section: Conceptualization Of Chemotherapeutics Driving Segmental Agingsupporting
confidence: 69%
“…Lastly, identification of toxicity-related biomarkers could aid in better monitoring and early detection of overtreatment and side-effects, while these are potentially still reversible. Better insight into development of side-effects facilitates the implementation of nutritional or chemical interventions to reduce toxicity [9,156,[167][168][169]. Patients can benefit from the aforementioned strategies, resulting in increased wellbeing, in both the short and long term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, 5,16–18,20 where significant differences were reported, CCS and references up to age 51 were included in the comparison. Cancer treatments might accelerate aging and put survivors at an increased risk of developing various health conditions earlier than the general population 39 . Therefore, differences between CCS and the general population with regard to problems with sexual functioning and sexual satisfaction may arise at a higher age than we were able to study.…”
Section: Discussionmentioning
confidence: 90%
“…DR increases health- and lifespan in organisms ranging from yeast to primates with benefits throughout the body ( Lee et al, 2021 ; Green et al, 2022 ). In rodents and primates, DR has been shown to reduce age-related decline in motor and cognitive function and age-related nervous system pathologies, and to increase resistance to oxidative, metabolic, and excitotoxic insults ( Valdez et al, 2010 ; Wahl et al, 2016 ; Mattison et al, 2017 ; van den Boogaard et al, 2021 ). Furthermore, DR has been shown to reduce neurological deficits and nervous system pathologies in a subset of mouse models for age-related neurodegenerative diseases ( Xie et al, 2020 ; Green et al, 2022 ; Mitchell and Mitchell, 2022 ).…”
Section: Introductionmentioning
confidence: 99%